Bone metabolism induced by denture insertion in positron emission tomography. (3rd October 2015) - Suenaga, H.; Chen, J.; Yamaguchi, K.; Sugazaki, M.; Li, W.; Swain, M.; Li, Q.; Sasaki, K.
Summary: 18F‐fluoride positron emission tomogra‐phy (PET) can identify subtle functional variation prior to the major structural change detectable by X‐ray. This study aims to investigate the mechanobiological bone reaction around the abutment tooth and in the residual ridge, induced by insertion of removable partial denture (RPD) within two different groups of patients: patients without denture experience (Group 1) and patients with denture experience before (Group 2), using 18F‐fluoride PET imaging technique. 18F‐fluoride PET/computerised tomography (CT) scan was performed to examine the bone metabolic change in mandible before and after the RPD treatment. Region of interests (ROIs) were placed in alveolar bone around abutment tooth and in residual bone beneath the RPD. Standardised uptake value (SUV), reflecting the accumulation of 18F‐fluoride, was measured for each ROI. In all subjects of Group 1, SUVs after insertion were higher than before in both alveolar bone and residual bone, while there was less significant change in SUV in subjects of Group 2. This study demonstrated using longitudinal 18F‐fluoride PET scans to effectively examine the bone metabolic change in mandible induced by occlusal loading after RPD insertion. Using this technique, within the six subjects in this study, it was shown that bone metabolism around abutment tooth and residual ridge increased after RPD insertion in case of first‐time denture user, while there was no big change in the patient with experience of denture before. This study revealed the effectiveness of applying PET to evaluate bone metabolic activity as mechanobiolo‐gical reaction.